BIODEGRADATION OF CHITOSAN MEMBRANE SCALES OF HARUAN FISH (Channa striata)-HYDROXYAPATITE IN ARTIFICIAL SALIVA SOLUTION - Syifa Kamila; Deby Kania Tri Putri; Amy Nindia Carabelly; Melissa Budipramana; Bambang Setiawan (Dentin, 2024)
Background: Membrane materials for surgical procedures using Guided Tissue Regeneration (GTR) are Polytetrafluoroethylene (PTFE) and collagen, but have the disadvantage of requiring further surgical procedures to remove membranes after use and rapid degradation properties. Haruan (Channa striata) fish scale chitosan is expected to be an alternative material for GTR membranes. Purpose: To determine the longer degradation time between chitosan membranes and chitosan+HA membranes in artificial saliva. Methods: This study used true experimental with post test only with control design using three treatments of 5% chitosan, 5% + 2 gr chitosan, and 5% + HA 4 gr of chitosan, positive control of GTR membrane with time intervals of 1, 7, 14, and 21 days in artificial saliva. Results: The results of the Kruskall Wallis test showed that there was a significant difference, the Mann Whitney Post Hoc test yielded 5% chitosan with chitosan+2 gr HA and chitosan+2gr HA with chitosan+4 gr HA had a p value <0.05 p=(0.000) in the 14th day, 5% chitosan with chitosan+4gr HA had a p value <0.05 p=(0.000) significant on days 7 and 14, and the positive control with all treatments had a p value <0.05 p=(0.000) . Conclusion: Chitosan and chitosan+HA membranes resulted in a degradation time of 21 days. Chitosan membrane + 2 g HA membrane was the best treatment because the remaining weight of the membrane was greater than the other treatments.Keywords : Channa striata, Chitosan, Degradation Test, Guided Tissue Regeneration (GTR), Hydroxyapatite, Remaining Membrane Weight